Cutting-edge advances in modeling the blood–brain barrier and tools for its reversible permeabilization for enhanced drug delivery into the brain - Sharma, A.; Fernandes, D. C.; Reis, R. L.; Gołubczyk, D.; Neumann, S.; Lukomska, B.; Miroslaw, J.; Kortylewski, M.; Walczak, P.; Oliveira, Joaquim M.; Maciaczyk, J. (Cell & bioscience, 2023)
The bloodâ brain barrier (BBB) is a sophisticated structure whose full functionality is required for maintaining the executive functions of the central nervous system (CNS). Tight control of transport across the barrier means that most drugs, particularly large size, which includes powerful biologicals, cannot reach their targets in the brain. Notwithstanding the remarkable advances in characterizing the cellular nature of the BBB and consequences of BBB dysfunction in pathology (brain metastasis, neurological diseases), it remains challenging to deliver drugs to the CNS. Herein, we outline the basic architecture and key molecular constituents of the BBB. In addition, we review the current status of approaches that are being explored to temporarily open the BBB in order to allow accumulation of therapeutics in the CNS. Undoubtedly, the major concern in field is whether it is possible to open the BBB in a meaningful way without causing negative consequences. In this context, we have also listed few other important key considerations that can improve our understanding about the dynamics of the BBB. The authors, DCF, RLR and JMO, would like to thank the funds under the project 2IQBIONEURO (reference: 0624_2IQBIONEURO_6_E) co-funded by INTERREG (Atlantic (Atlantic program or 622 V-A Spain-Portugal) and European fund for Regional Development (FEDER). Open Access funding enabled and organized by Projekt DEAL.